Stanislavsky (Princeton, N.J. Films for the Humanities and Sciences, 1972)
Provides a glimpse of the man whose precepts of "truth in art" have torched every dramatic production and work of the last century, showing his theories and thier execution.
VHS
Narrated by Paul Rogers.
Keywords: Stanislavsky, Konstantin, 1863-1938.; English drama -- 20th century; Theater -- History -- 20th century. -- Russia (Federation) -- Moscow; Theater -- History. -- Russia (Federation) -- Moscow